Comparative sport development : systems, participation and public policy - Petry, Karen (Sports Economics, Management and Policy,, 2013)
The aim of this book is to provide an overview of perspectives and approaches to sports development focusing on sport systems, sport participation and public policy towards sports. It includes twelve European countries covering all regions of Europe and eleven countries from around the globe. The objective is to present an overview of the diversity of approaches taken to sport development, focusing on the different sport systems and how sport is financed, the underlying applications of sport policy and how it is reflected in sport participation. This book takes a comparative approach which is reflected in each chapter following a similar structure. The diversity of sports systems in Europe and other continents and their (historical) context is shown. Thereby a range of policy approaches underpinning sport development around the world are presented, making it of interest to both academics and policy-makers concerned with sports economics and policy.